2016
DOI: 10.1515/anre-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination from femora in late antique sample from Eastern Adriatic coast (Salona necropolis)

Abstract: The determination of sex is one of the first steps in anthropological analysis. When skeletal remains are fragmented, the most useful approach is application of osteometric methods. The methods are population specific, and therefore require development of discriminant functions for each population group. The aim of this study was to test sexual dimorphism of femoral measurements and to calculate discriminant functions applicable for sex determination on fragmented skeletal remains on the late antique sample fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Deriving the discriminant function based on the measurements of individuals whose sex was estimated using anthropological methods is prone to error. However, this approach is not new and skeletons with unknown sex were used e.g., for the creation of the first sex discrimination function for the Iron Age population from Iran, using dental measurements (Kazzazi and Kranioti 2018) or for calculating formula for late antique East Adriatic coast population (Jerković et al 2016). The need for metric methods for sex estimation is strong.…”
Section: Discussionmentioning
confidence: 99%
“…Deriving the discriminant function based on the measurements of individuals whose sex was estimated using anthropological methods is prone to error. However, this approach is not new and skeletons with unknown sex were used e.g., for the creation of the first sex discrimination function for the Iron Age population from Iran, using dental measurements (Kazzazi and Kranioti 2018) or for calculating formula for late antique East Adriatic coast population (Jerković et al 2016). The need for metric methods for sex estimation is strong.…”
Section: Discussionmentioning
confidence: 99%
“…Though our models are constrained by this relatively small sample of modern Egyptians, there seems a number of methods in the literature based on small sample size of poorly preserved archaeological assemblages (Dabbs, 2010; MacLaughlin & Bruce, 1985). Missing values reduce the available sample for the calculation of multivariate models (Cardoso, 2008; Jerković et al, 2016). Notwithstanding, Hora & Sládek, 2018 had demonstrated that models derived from a sample of estimated sex with a size as small as ( n = 30–34) could provide accurate and consistent sex classification in the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…Although mid‐shaft measurements were reportedly accurate in sexing of femora, their application is not without caveats (Albanese et al, 2005; MacLaughlin and Bruce, 1985). There is uncertainty associated with determination of the mid‐shafts location due to difficulties in femur length estimation in cases of fragmentary remains and lack of anatomical landmarks (Jerković, Bašić, Kružić, & Anđelinović, 2016; Nakahashi & Nagai, 1986; Wrobel et al, 2002). Therefore, the present investigation seeks to develop a method based on nutrient foramina as a landmark for measurement in absence of both epiphyseal ends of femur.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step, we assessed the degree of preservation of remains and reconstructed biological profile of the person. Sex was assessed by examination of the pelvic traits (Phenice, 1969;Walker, 2005) and discriminant functions for femora (Jerković, Bašić, Kružić, & Anđelinović, 2016), and age of death was estimated using morphological changes on pubic symphysis (Brooks & Suchey, 1990) and degree of epiphyseal fusion (Schaefer, Black, & Scheuer, 2009). The average height of the person was estimated using maximum femoral length (Trotter & Gleser, 1952).…”
Section: Macroscopic Examinationmentioning
confidence: 99%